2011
DOI: 10.1007/bf03325322
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders and diabetic ketoacidosis in a pregnant woman with type 1 diabetes: A case report

Abstract: We suggest that pregnancy in T1DM women with eating disorders may not be rare. The prevention, early recognition and aggressive management of DKA can minimise the possible complications, and is mandatory for the safety of the fetus and mother.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…25,30,31 Furthermore, it has been suggested that the development of diabetic ketoacidosis and starvation in the pregnant type 1 diabetic with eating disorders may not be rare. 32 In addition, the increased minute alveolar ventilation places the pregnant woman in a state of respiratory alkalosis and is counterregulated by increased renal excretion of bicarbonate. This results in a lowered buffering capacity, which further contributes to the development of diabetic ketoacidosis at lower glycemic levels than those seen in nonpregnant patients.…”
Section: Metabolic Considerations Unique To Pregnancymentioning
confidence: 99%
“…25,30,31 Furthermore, it has been suggested that the development of diabetic ketoacidosis and starvation in the pregnant type 1 diabetic with eating disorders may not be rare. 32 In addition, the increased minute alveolar ventilation places the pregnant woman in a state of respiratory alkalosis and is counterregulated by increased renal excretion of bicarbonate. This results in a lowered buffering capacity, which further contributes to the development of diabetic ketoacidosis at lower glycemic levels than those seen in nonpregnant patients.…”
Section: Metabolic Considerations Unique To Pregnancymentioning
confidence: 99%
“…Of the 17 included studies, 15 studies addressed the use of CSII in people with T1DM and disordered eating. 11,12,[34][35][36][37][38][39][40][41][42][43][44][45][46] Three studies referred to CGM (two of which also addressed CSII), 38,39,47 and one study referred to the use of AID in people with T1DM and disordered eating 48 (Table 1). Fourteen studies, thirteen with observational and one with controlled design, were eligible for quality assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies, thirteen with observational and one with controlled design, were eligible for quality assessment. Two case studies 40,41 and one review 48 included in our synthesis were not assessed in terms of their quality. Eight studies were classified as having a moderate risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, it is recommended to continue the pregnancy while attempts are made to identify and correct the physiologic derangement. Typically, once the acidosis is corrected, fetal abnormalities improve [4, 12 16]. Emergent cesarean delivery should only be attempted if the maternal condition worsens, but this is associated with high maternal morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%